Environmental History, The History of Tourism in the Mountains and the Construction of New Knowledge: A Study of the Architecture of Winter Sports Resorts in the French-Italian Alps - Caterina Franco (Revue de Géographie Alpine)
Environmental history is a rapidly developing field of study. In keeping with the ecological, energy and health issues that affect contemporary societies, it is important to understand the past by examining the interactions between human and natural factors. This interest is particularly evident in work on the Alps and mountains in general. Our contribution relates and adds to studies focused on the history of tourism in the Alps and assesses the capacity of environmental history to produce a renewed knowledge. Moreover, it investigates the specificity of the Alps and the mountains as a privileged field of study for environmental history. After outlining recent scientific output from around the world based on environmental history, we present the results obtained through a research experiment on the history of winter sports resorts in the French-Italian Alps. Understanding the relationships between the evolution of the projects and the natural and historical components of the sites where they are located and extending the spatial and temporal frameworks of the analyses and the use of multiple sources will clarify how tourism develops in high-altitude areas. Our work invites researchers to move beyond the image of infrastructure built “ex nihilo” or on so-called “virgin” sites and a narrative limited to the period of the “Trente Glorieuses” to reveal the dynamics of how a territory transforms over time.